Comparison of the efficacy and safety of various anti-inflammatory drugs in urate-lowering therapy initiation in patients with gout (preliminary data) - M. N. Chikina; M. S. Eliseev; O. V. Zhelyabina (Современная ревматология)
Non-steroidal anti-inflammatory drugs (NSAIDs), colchicine and glucocorticoids (GC) are used to prevent arthritis attacks in gout, but data on their comparative effectiveness is lacking.Objective: to compare the efficacy and safety of various anti-inflammatory drugs at the start of treatment in patients with gout.Patients and methods. Of the 108 patients with gout, observed in the V.A. Nasonova Research Institute of Rheumatology, 97 (94%), mostly men, entered a single-center prospective study. The observation period was at least 24 weeks, patients received combined urate-lowering and prophylactic anti-inflammatory therapy unintermittingly. The control group included 12 patients in whom anti-inflammatory drugs were contraindicated. At the start of urate-lowering therapy, allopurinol 100 mg per day was prescribed, followed by dose titration until the target uric acid (UA) level of < 360 μmol/L level was reached, in patients with severe tophus gout it was < 300 μmol/L. The maximum dose of allopurinol was 900 mg per day; in patients with reduced glomerular filtration rate (<60 ml/min/1.73m2 ) – 300 mg per day. For the prevention of arthritis attacks, the drug of choice was colchicine 0.5 mg per day, when contraindicated and/or poorly tolerated, NSAIDs were prescribed in the minimum effective dose. If there were any NSAIDs use restriction or intolerance – prednisone 7.5 mg per day was administered. The effectiveness of anti-inflammatory therapy (NSAIDs, colchicine or GC) was evaluated after 3 and 6 months which included analysis of the frequency of exacerbations and the duration of arthritis attacks, the intensity of pain according to the visual analogue scale (VAS) during a gout attack.Results and discussion. Of 97 patients with gout, 85 (88%) received anti-inflammatory therapy: NSAIDs – 16 (19%), colchicine – 60 (71%), GC – 9 (10%). In 65% of patients who were administered anti-inflammatory therapy, there were no recurrence of arthritis, whereas in 12 patients of the control group who did not receive this treatment, recurrence of arthritis was absent only in 25% of cases (p=0.008). After 3 and 6 months of follow-up, the duration of gout attacks and the intensity of joint pain according to the VAS for recurrent arthritis were significantly less (p< 0.05 in both cases) in the treatment group (with any anti-inflammatory drug) than without treatment. Arthritis attacks were more likely to be absent when taking NSAIDs than when using colchicine and GC both after 3 (63%) and 6 (81%) months (p< 0.05 in both cases). After 3 months of observation, the intensity of pain according to the VAS during the development of a gout attack was less for NSAIDs therapy than for colchicine and GC (p< 0.05 in both cases), and after 6 months there was no difference between NSAIDs, colchicine and GC. Within first 3 months, there was no difference in the duration of arthritis attacks among anti-inflammatory drugs, whereas after 6 months duration of attacks was the smallest for NSAID therapy (p< 0.05). Adverse reactions occurred only in NSAID and colchicine therapy in 2 and 5 patients, respectively. The patient's refusal to continue therapy without cause occurred in 13 (15%) cases, more often when taking colchicine.Conclusion. The proposed algorithm of anti-inflammatory drugs prescription for prevention of arthritis recurrence can reduce the risk of gout attacks development with good tolerance of the therapy. At the same time, better control of the frequency and duration of arthritis attacks, as well as the intensity of pain according to the VAS, is observed with the use of NSAIDs than with the use of colchicine and GC.